DETERMINANTS OF PROFITABILITY OF NIGERIAN DEPOSIT MONEY BANKS - Wasiu Abiodun Sanyaolu; Trimisiu Tunji Siynbola; Gbadebo Tirimisiyu Ogunmefun; Afeez Babatunde Makinde (Economic Review)
This study investigates banks’ specific and macroeconomic determinants of profitability of ten listed deposit money banks in Nigerian Stock Exchange from 2008 to 2017 using fixed effect regression. The result reveals that capital adequacy, nonperforming loan, loan to total asset and size have significant positive effect on profitability, while age was found to exert significant but negative effect on profitability. The study could not however establish significant positive effect of macroeconomic indicators (economic growth and interest rate) on profitability of deposit money banks while inflation rate has negative but insignificant influence on profitability. Arising from the findings, the study recommends that government should initiate and execute economic policies that will improve the profitability of deposit money banks in Nigeria given the key role of the sector to the economy while banks should also manage their specific variables that are likely to improve profitability.